Successful Diagnosis of Hypothalamitis Using Stereotactic Biopsy and Treatment: A Case Report. Issue 5 (February 2015) - Zhang, Shuo; Ye, Hongying; Zhang, Zhaoyun; Lu, Bin; Yang, Yehong; He, Min; Wu, Hanfeng; Zhou, Linuo; Wang, Yin; Pan, Li; Li, Yiming; Hu, Renming
Abstract : Abstract: Existing methods could not discriminate between inflammation and other diseases, which might occur in hypothalamus, such as neurogliocytoma, germinoma, lymphoma, and so on. Given its location in the brain, it was not practical to obtain tissue using standard surgical methods. We reported the first case of a patient with hypothalamus lesion, who was diagnosed as hypothalamitis by stereotactic biopsy. This precise diagnosis allowed proper medical treatments. We reported a case of a patient with hypothalamus lesion. To confirm the diagnosis, with informed consent from the family, a successful stereotactic hypothalamic biopsy was performed by neurosurgeons. Immunohistochemical results of biopsy specimens from the hypothalamus lesion revealed inflammatory infiltrates, which were composed mainly of lymphocytes, plasma cells, and histiocytes, and were stained with leucocyte common antigen (LCA), κ 1, and cluster of differentiation 18. Final pathological diagnosis was lymphoplasmacytic proliferative, granuloma-like inflammatory pseudotumor, with immunoglobulin G deposition. Based on the pathological diagnosis, we treated the patient with glucocorticoid and azathioprine. Remarkable improvements were observed in both magnetic resonance imaging (MRI) and patient's symptoms. Stereotactic biopsy for intracranial lesions was a reliable and relatively safe procedure, even for hypothalamus. It was an effective method with high diagnostic yield. With correct diagnosis, it was much easier to choose correct treatment.